A Novel Flavone Glycoside From the Stems of Dalbergia Sympathetica - Yadava, R.N.; Roy, Anila (Asian Journal of Chemistry, 2010)
A novel flavone glycoside isolated from the stems of Dalbergia sympathetica and its structure was identified as 5,7-dihydroxy-4'methoxy flavone-5-O-α-L-rhamnopyranosyl (1→6)-O-β-D-galactopyranoside by various chemical reactions and spectral analysis.